Toxic and trace metal contents in six species of fish from istanbul boshphorus, Turkey - (:unkn) unknown (My University, 2010)
Toxic and essential metal content of six different fish species from Istanbul Bosphorus were determined by ICPMS after microwave digestion method. The validation of the presented procedure was performed by the analysis of standard reference materials (NRCC-DORM 2 Dogfish Muscle). The relative standard deviations were found to be lower than 10%. Toxic metal contents in fish samples were 0.123-0.312 mg/kg for lead, 0.029-0.065 mg/kg for arsenic, and 0.085-0.113 mg/kg for mercury. Trace metal content in fish samples was 0.303-1.343 mg/kg for copper, 4.761-13.016 mg/kg for zinc and 0.438-0.596 mg/kg for selenium. Cadmium could not be found in any fish samples. The lead level in M.surmuletus was found to be higher than defaulted by the Turkish Food Codex. Generally, copper, zinc, mercury , arsenic and selenium levels in analysed fish samples were found to be in agreement with the literature values. © by PSP.
Keywords: Digestion; Fish; ICPMS; Istanbul boshphorus; Toxic metals; Trace metals